Measuring Service Quality at Public Service Mal in Tangerang City - Hidayat, Evanito Nur; Stiawati, Titi (Epistemik Press, 2024)
Based on Law Number 25 of 2009, it can be interpreted that the Government is obliged to serve the rights and needs of the community as citizens through public services. To achieve better public services, the Government innovates services through Public Service Malls (MPP) so that everyone can access government services easily and quickly without exception. One of the Public Service Malls (MPP) is held in Tangerang City, the research locus. Implementing this service innovation is directed at public satisfaction with government services. In conducting this research was carried out using descriptive quantitative methods. This research also has limitations, namely in discussing how high the quality of service is at the Tangerang City Public Service Mall (MPP) and carried out on the population of people using the Tangerang City Public Service Mall (MPP) with a total of 74,422 users. Sampling was conducted using the Slovin formula with a MoR of 10%, namely 100 respondents. This research also aims to prove the magnitude of the influence that the implementation of QRIS has on purchasing interest. To support this, respondents were determined as one of the instruments, namely using the Purposive Sampling Technique. This research shows that the Public Service Quality score at the Tangerang City Public Service Mall reached a value of 75% or obtained a percentage result of more than 60%. Of course, it is necessary to provide supporting facilities such as digital services, facilities for pregnant women or people with disabilities, a clean MPP environment, and increased human resources for service staff. The 75% service quality score at the Tangerang City Public Service Mall (MPP) was also declared good.